Characterization of fluid occurrence states in shale reservoirs: centrifugal–nuclear magnetic resonance experimental analysis - Jin Pang; Tongtong Wu; Xinan Yu; Chunxi Zhou; Haotian Chen; Jiaao Gao (Royal Society Open Science)
The occurrence states of fluids in shale reservoirs directly influence the resource assessment of shale gas, reservoir permeability, selection of development technologies and economic benefits. Accurate analysis of fluid occurrence states is a key foundation for the efficient exploration and development of shale gas. To comprehensively elucidate the fluid distribution characteristics within shale pores, this study integrates centrifugation–nuclear magnetic resonance (NMR) experiments with stepwise thermal drying and methane adsorption analyses. By examining the NMR T₂ spectra of shale samples under varying centrifugal speeds, the distinction between movable and bound fluids is established, clarifying the influence of pore structure on fluid occurrence. Quantitative relationships between pore size and adsorbed/free gas are further investigated through methane adsorption experiments. Results demonstrate that centrifugation progressively removes water from macropores and microfractures, leaving residual water mainly confined to micropores. The stepwise thermal drying method efficiently differentiates movable water, capillary-bound water and clay-bound water. Integrating NMR analysis with methane adsorption reveals a significant impact of pore size on fluid occurrence: micropores predominantly store adsorbed gas, whereas macropores mainly contain free gas. These findings provide a theoretical basis for shale gas development and furnish essential data for optimizing exploration and production techniques.